Aminoalkylated Merrifield Resins Reticulated by Tris-(2-chloroethyl) Phosphate for Cadmium, Copper, and Iron (II) Extraction - Mokhtar Dardouri; Fayçel Ammari; Faouzi Meganem (International Journal of Polymer Science)
We aimed to synthesize novel substituted polymers bearing functional groups to chelate heavy metals during depollution applications. Three polyamine functionalized Merrifield resins were prepared via ethylenediamine (EDA), diethylenetriamine (DETA), and triethylenetetramine (TETA) modifications named, respectively, MR-EDA, MR-DETA, and MR-TETA. The aminoalkylated polymers were subsequently reticulated by tris-(2-chloroethyl) phosphate (TCEP) to obtain new polymeric resins called, respectively, MR-EDA-TCEP, MR-DETA-TCEP, and MR-TETA-TCEP. The obtained resins were characterized via attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), elemental analysis (EA), and thermogravimetric (TGA), thermodynamic (DTA), and differential thermogravimetric (DTG) analysis. The synthesized resins were then assayed to evaluate their efficiency to extract metallic ions such as Cd2+, Cu2+, and Fe2+ from aqueous solutions.